Case report: Malaria and hepatitis E coinfection—first experience with such imported entity in Serbia - Ranković, Aleksandar; Cvetanović, Maja; Miladinović, Jelena; Ćosić, Milica; Popović Dragonjić, Lidija (Frontiers in Medicine, 2024)
Acute hepatitis E virus (HEV) and malaria are not rare infections in tropical countries; however, in the European continent, such imported entity has not been reported up to now. Herein, we report a 24-year-old male suffering from malaria and hepatitis E, who was admitted with acute hepatic failure dark colored urine, followed by coagulation and inflammation parameters increase. Blood smear analysis revealed the presence of Plasmodium falciparum, while serological tests revealed anti-HEV IgM antibodies. After the recommended antimalarial drugs and supportive therapy, the patient survived and was discharged disease-free. Conclusions: Following WHO guidelines for the treatment of severe malaria, full recovery in patient was achieved.